الدور الاستشاري لمجمس الدولة الج ا زئري في ظل التعديل الدستوري 20 - ناصري عمي, علي (University of Eloued جامعة الوادي, 2020)
إن دراستنا للاختصاصات الاستشارية لمجلس الدولة الجزائري والتي تتمثل في إبداء رأيها في مشاريع القوانين التي يبادر بها رئيــس الحكومة تبين لنا ان المجال الذي تمتد اليه هذه الاختصاصات يتمثل في الجانب التشريعي فقط وهذا هو الذي جعل مجال الاستشارة يتسم بالضيق خلافا لصفة الاتساع التي تتميز بها الانظمة المقارنة التي تأخذ بالازدواجية والتي تشمل حتى الجانب الاداري من (-المراسيم – القرارات الوزارية-.......) ، ورغم أن المادة 142 من دستور 2016 وسعت من مجال استشارة مجلس الدولة وأخضع أوامر رئيس الجمهورية المتخذة خلال شغور المجلس الشعبي الوطني أو العطل البرلمانية أو في حالة المسائل العاجلة إلى أخذ رأيه بقولها "‬لرئيس الجمهوريّة أن يشرّع بأوامر في‮ ‬مسائل عاجلة في حالة شغور المجلس الشّعبيّ الوطنيّ‮ ‬ أو خلال العطل البرلمانية،‮ ‬بعد رأي‮ ‬مجلس الدولة"‮، لكن مجلـس الدولـة ورغم حداثتـه والعوائق المختلفـة التي تحول دون تقدمه يتطلع إلى تحقيـق كل المهـام الموكولة إليـه على أحسن وجـه، لا سيما أن الفرصة متاحـة اليوم في إطار إصلاح العدالة وتدعيم أسس دولـة القانـون إذ تحدو أعضـاء مجلس الدولـة الرغبة في رفع الرهانان المنوطـة بمؤسستهـم لأنهم يعتقدون أن تشييد دولـة القانـون هو فعلا رهـان كـل مجتمع ينشــد العدالـة أولا وأخيـرا ..Our study of the advisory competencies of the Algerian Council of State, which is represented in expressing its opinion on draft laws initiated by the head of government, shows us that the area to which these specializations extend is represented in the legislative aspect only, and this is what made the field of consultation characterized by a narrow, contrary to the wide characteristic of the comparative systems Which is adopted in duplication, which includes even the administrative aspect of (- decrees - ministerial decisions - ... ...), although Article 142 of the 2016 Constitution expanded the field of consulting with the State Council and subjected the President of the Republic orders made during the vacancy of the National People's Assembly or holidays Parliamentary or urgent matters to take his opinion by saying, "The president of the republic may legislate by orders in urgent matters in the event of the vacancy of the National People's Assembly or during parliamentary holidays, after the opinion of the State Council." However, the State Council, despite its modernity and the various obstacles that prevent its progress, aspires to achieve all the tasks entrusted to it in the best manner, especially since the opportunity is available today in the framework of reforming justice and strengthening the foundations of the state of law. Building a state of law is, in fact, the pledge of every society that seeks justice first and foremost.
مذكرة ماستر